Examining Memorizing Al-Qur’an Ability Towards Vocabulary Mastery and Reading Comprehension at the Eighth Graders of SMP ABBS Surakarta - Sundari; Budiharso, Teguh; Retnaningsih, Woro; Muntaha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aimed to examine the effect of Al-Qur'an memorization on vocabulary mastery and reading comprehension. The research design was correlational, involving a sample of 27 eighth-grade students from SMP ABBS Surakarta. Data collection included tests on vocabulary mastery and reading comprehension, as well as Al-Qur'an memorization scores provided by the Tahfiz teacher. Data analysis was conducted using the SPSS application. The results indicate the following: First, there is a significant effect of Al-Qur'an memorization on vocabulary mastery, with an R2 value of 0.460, meaning that memorizing the Al-Qur'an contributes 46% to students' English vocabulary mastery. Second, Al-Qur'an memorization also significantly affects students' reading comprehension, with an R2 value of 0.334, indicating that it accounts for 33.4% of the improvement in reading comprehension.